1993
DOI: 10.1080/00913367.1993.10673405
|View full text |Cite
|
Sign up to set email alerts
|

The Operation of Visual Imagery as a Mediator of Advertising Effects

Abstract: Advertising strategists should be interested in visual imagery because it may represent a useful way to shape consumers' impressions. A framework is tested which casts visual imagery as a mediating factor and individual differences, such as style ofprocessing, as potential moderators of certain advertising strategies which elicit attitude and intentions differences in consumers. Results indicate that the vividness of visual imagery does operate as a latent cognitive construct when concrete wording is used in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
126
2
3

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(137 citation statements)
references
References 43 publications
6
126
2
3
Order By: Relevance
“…Paivio, 1971;Rossiter, 1978;Babin, Burns & Biswas, 1992;Burns, Biswas & Babin, 1993;Babin & Burns, 1997), little empirical research exists that deals with the effects of text formats on mental imagery processing. Brewer (1988) claims that text genre can indeed be an important factor in encouraging mental imagery processing and Lee et al (2010) also found textual qualities of destination Web sites to matter.…”
Section: Narrative Information Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…Paivio, 1971;Rossiter, 1978;Babin, Burns & Biswas, 1992;Burns, Biswas & Babin, 1993;Babin & Burns, 1997), little empirical research exists that deals with the effects of text formats on mental imagery processing. Brewer (1988) claims that text genre can indeed be an important factor in encouraging mental imagery processing and Lee et al (2010) also found textual qualities of destination Web sites to matter.…”
Section: Narrative Information Processingmentioning
confidence: 99%
“…According to Burns, Biswas and Babin (1993), this mental imagery can be experienced in different sensory modalities and can vary in terms of vividness and quantity. Research on imagery has provided strong evidence that elaborate imagery processing may positively influence decision outcomes (Babin & Burns, 1997;Bone & Ellen, 1990).…”
Section: Mental Imagery Processing and Persuasionmentioning
confidence: 99%
See 1 more Smart Citation
“…These hypotheses were 7 tested by running a MANOVA (Table 1) with summed and averaged index scales for the three 8 imagery dimensions (Babin et al 1993) and it showed a significant effect of for the type of 9 messages (Wilks lambda = .799, F = 13.996, p < .000). The ANOVA results indicated that 10 visual mobile ads boosted the imagery process, increasing vividness and elaboration in a 11 significant way; however, and despite the fact that it is also significant, the difference in 12 quantity suggests that SMSs are better at boosting a great number of mental images (Table 2).…”
mentioning
confidence: 99%
“…Th e existing fi ndings converge across a variety of products, such as automobiles (Burns, Biswas, & Babin, 1993;McGill & Anand, 1989), beer (Rossiter & Percy, 1978), apartments (Keller & McGill, 1994;McGill & Anand, 1989), restaurants (Petrova & Cialdini, 2005), cameras (Schlosser, 2003), and vacations (Adval & Wyer, 1998;Krisnamurty & Sujan, 1999;Petrova & Cialdini, 2005). However, all of these product categories have an experiential component, and the product use has been associated with positive aff ect.…”
Section: When Does Imagery Infl Uence Consumers' Judgments?mentioning
confidence: 99%